Pembuatan Power Point sebagai Upaya Guru Meningkatkan Kreativitas Siswa Sekolah Dasar Menggunakan Fasilitas di BITC Bandung - Ahsani, Eva Luthfi Fakhru; Zuhaida, Khusna; Putri, Mutiara Ananda; Jannah, Asna Fathul; Arumdiyah, Ita Amalia (Lembaga Yasin AlSys, 2022)
The aim of this study to provide an overview of teachers,especially elementary school teachers about making creative and innovative power points that can increase the creativity of elementary school students in the field of information and technology. This research uses a qualitative descriptive analysis technique at BITC Bandung. The problem that occurs in elementary schools is that teachers do not know how to take advantage of creativity that has been made by students, especially in learning information and communication technology.This result of this study indicate that efforts to increase the creativity of elementary school students can be done by making creative and innovative power point supported by facilities at BITC Bandung to be published through the market place like envato and shutterstock.